2001
DOI: 10.1029/2001gl013565
|View full text |Cite
|
Sign up to set email alerts
|

QBO signal found at the extratropical surface through northern annular modes

Abstract: Abstract.A QBO (quasi-biennial oscillation) signal is found in 150-year, Northern Hemisphere, surface air temperatures which have been projected onto an annular mode at the surface. The signal is tied to the equatorial QBO by demonstrating coherence in the extratropical stratosphere and tracing the signal, using the annular modes as a filter, down through the atmosphere to the surface. Then the statistical significance of the surface signal is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…As discussed in another paper in this volume (Kodera 2001) and in Shindell et al (2001), volcanic aerosols and polar stratospheric ozone losses also seem to impact tropospheric circulations. The QBO by itself appears to affect tropospheric northern annular modes (Coughlin and Tung 2001). All these forcings seem to involve the same process-alteration in temperature gradients and zonal wind in the upper troposphere and stratosphere, affecting tropospheric wave propagation and tropospheric angular momentum transport.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in another paper in this volume (Kodera 2001) and in Shindell et al (2001), volcanic aerosols and polar stratospheric ozone losses also seem to impact tropospheric circulations. The QBO by itself appears to affect tropospheric northern annular modes (Coughlin and Tung 2001). All these forcings seem to involve the same process-alteration in temperature gradients and zonal wind in the upper troposphere and stratosphere, affecting tropospheric wave propagation and tropospheric angular momentum transport.…”
Section: Introductionmentioning
confidence: 99%
“…Collimore et al 1998, 2003, Giorgetta et al 1999Baldwin et al 2001). Also high latitude changes of the stratospheric polar vortex are thought to impact mid and high latitude tropospheric weather and climate, for example through changes in the North Atlantic Oscillation and position of the jet stream (Thompson and Wallace 2000;Coughlin and Tung 2001;Baldwin et al 2003;Dall'Amico and Egger 2007). Stenchikov et al (2004Stenchikov et al ( , 2006 have shown that inclusion of the equatorial QBO influences the high latitude volcanic response in the stratosphere and also at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore to be distinguished from the direct continuation of the stratospheric QBO into the (mainly midlatitude) troposphere, as reported by e.g. Coughlin and Tung (2001), Crooks and Gray (2005) and Garfinkel and Hartmann (2011). In addition, the Indian and West Pacific monsoon indices are themselves mutually coherent on quasi-biennial time-scales (section 3.4) and at least partly coherent with other tropical climate indices, such as those for West African rainfall, which also feature in schemes for seasonal forecasting e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence has suggested the direct penetration of the stratospheric QBO into the lower atmosphere, as manifest e.g. in variations of midlatitude surface pressure and zonal winds (Coughlin and Tung, 2001;Crooks and Gray, 2005;Garfinkel and Hartmann, 2011). The stratospheric QBO has thus been associated with cyclic variations in hurricane activity in the Atlantic, for example, such that QBO indices are commonly used as a component in the seasonal forecasting of tropical cyclones (Gray, 1984a,b).…”
Section: Introductionmentioning
confidence: 99%